MAPPING AND CLASSIFICATION OF DIRECT EFFECTS OF THE FLOOD OF OCTOBER 2014 IN ATHENS - Diakakis, M.; Deligiannakis, G.; Katsetsiadou, K.; Lekkas, E.; Melaki, M.; Antoniadis, Z. (Bulletin of the Geological Society of Greece, 2016)
In 24 October 2014, a high intensity storm hit Athens’ western suburbs causing extensive flash flooding phenomena. The drainage and the sewerage network of the city were overwhelmed leading to catastrophic flood flows along the road network, flooding houses and businesses, sweeping away vehicles, injuring people and causing numerous problems in transportation across the city. Parts of the city were inundated for several hours, particularly in western Athens, namely Ilion, Menidi, Peristeri, Acharnai, Korydallos and Piraeus. This work examines and reconstructs in detail the flood’s characteristics, the different types of direct effects within the urban environment and the severity of its direct impacts across Athens basin. Results show a concentration of flood damages in specific locations mostly along the city’s natural drainage network or derelict streams and culverts. At their peak stage, floodwaters extended to an area of 4.9 square km recording a maximum depth of 170 cm in certain locations. Eight types of direct impacts were identified in 1223 impact locations, including effects on vegetation, geomorphology, erosion, mobile objects, buildings, infrastructure and human population. A severity scale was developed allowing effects to be divided in five severity classes across the flooded area and making possible the delineation of high impact sections of the city.